Advanced materials XV International Symposium on Advanced Materials Islamabad, Pakistan : selected, peer reviewed papers from the 15th International Symposium on Advanced Materials (ISAM-2017), October 16-20, 2017, Islamabad, Pakistan (Key engineering materials, 2018)
This book is the proceedings of the 15th International Symposium on Advanced Materials (ISAM-2017, October 16-20, 2017, Islamabad, Pakistan) and contains the selected peer reviewed papers which reflect recent achievements in the field of materials sciences and technologies of their processing and synthesis. We hope that this collection will be useful and interesting for the wide range of researchers and engineers.